Leadership development within a Learner Representative Council (LRC) in a rural secondary school in the Oshana region, Namibia - Da Silva, Rolens (Rhodes University, Faculty of Education, Department of Education, 2018)
The Namibian Education Act (Namibia. Education Act No. 16 of 2001) mandates state secondary school learners to be included in school leadership through a body of learners known as the Learner Representative Council (LRC). The few studies carried out on the LRC in schools reveal that very little has been achieved in terms of learner leadership development. This study explored and provided insight into possible reasons for this, and recommendations. The research questions driving the study were: How is learner leadership currently understood and practised in the school? What are the enabling and constraining factors in the school as far as learner leadership development is concerned? And what can be done to promote learner leadership development? This study is an interpretive case study of learner leadership in the LRC in a Namibian state secondary school in the Oshana region. The conceptual framework used was distributed leadership. The Cultural Historical Activity Theory (CHAT) was used as an analytical tool. The research participants were the LRC members, school principal, Heads of Departments representing the school management members, the School Board Chairperson representing parents and the LRC liaison teacher and were all purposively selected. Data was collected through document analysis, open-ended questionnaires, interviews and non-participant observation. Data analysis took the form of inductively "“ identifying themes emerged from the data and deductively "“ using CHAT to surface the systemic contradictions within the learners' activity system. The data revealed that learner leadership was mostly understood from a management perspective and equated with the formal authority of the LRC in the school. The data further revealed that the LRC performed more leadership roles stretched from inside the classroom, outside the classroom, on the School Board and outside the school. To capture this complexity, I developed a model which may prove useful for future studies of learner leadership. The data also indicated that much support was offered to the LRC members in the school; for example, support from the LRC liaison teacher, the School Management Team and generally from the school, through LRC leadership training. Using CHAT, the findings revealed that the historical context and cultural conventions contradicted the LRC leadership development in the school. In line with a distributed leadership theory, the study recommends that learner leadership should not be limited by position and authority but should be exercised by all learners, through the development and establishment of learner leader clubs in the school. The study also recommends that schools should embark on change initiatives which challenge their traditionally held beliefs and attitudes.
Keywords: Student participation in administration-- Namibia; Student government-- Namibia; Educational leadership-- Namibia; Qualitative research